Estructura y distribución de la regeneración natural de dos especies maderables del bosque andino - Zúñiga Chacón, Cinthya Sofía (2024)
The Andean forests are important for the preservation of biodiversity; however, they face threats such as land-use conversion, selective logging, and fires that cause their degradation, putting the evolution of natural forest populations at risk. Cedrela montana Moritz ex Turcz. and Nectandra laurel Klotzsch ex Nees have great potential within the forestry sector. Therefore, this research was conducted with the objective of characterizing the structure and spatial distribution of the natural regeneration of these two timber species in the Andean forest within the "Francisco Vivar Castro" University Park. Five individuals of each species were selected, with a diameter at breast height (DBH) greater than 5 cm, and the variables of crown position, diameter at breast height, and geographical location of the tree were measured. Transects were installed according to the cardinal orientation North (N); South (S); East (E); West (W), with an area of 20 x 5 m, and each transect was divided into five subplots of 4 x 5 m to identify and measure the height of the regeneration, categorizing them into seedling, sapling, and young tree stages; additionally, the quality of the regeneration was evaluated (good, fair, poor). Structural parameters such as density and relative density were calculated. For the spatial distribution analysis, the distances of the subplots and the cardinal orientation were considered. The results showed differences in the structure of natural regeneration; thus, Cedrela montana recorded 235 individuals, 46% of which were seedlings, 51% saplings, and 13% young trees. Regarding spatial distribution, the highest amount of regeneration was found at a distance of 8 to 12 m towards the East; whereas for Nectandra laurel, 348 individuals were identified, of which 28% were seedlings, 53% saplings, and 19% young trees, with the highest distribution located at 4 to 8 m towards the South. Cedrela montana has individuals in all regeneration categories; however, a considerable reduction in the young tree category suggests it is being affected in the early stages. In contrast, Nectandra laurel is more homogeneously represented in all three categories, indicating a population status that would ensure its permanence in the Andean forest over time. For both species, the sapling category is the best represented. The information obtained contributes to the ecology, conservation, and forest management of these timber species.